Novel method for the detection of nitroglycerin in smokeless powders. Issue 6 (December 2015) - Roberts, Marcel; Petraco, Nicholas; Gittings, Michael
Abstract: Nitroglycerin is an active component in many explosive substances. Notably, it is found as an active ingredient in double-base smokeless powders, differentiating them from single-base powders, whose main active ingredient is nitrocellulose. It is proposed that the detection of nitroglycerin within various types of ammunition will allow for the differentiation between single and double-base smokeless powders, thus allowing for a method of distinguishing ammunition or bulk powder samples that may be found during the course of a criminal investigation. Presumptive tests are an effective tool in field-testing for forensic science. These tests are used primarily as rapid, sensitive means of elucidating the chemical characteristics of an unknown sample in-situ . In this paper, the authors present a novel method for the detection of nitroglycerin in smokeless powders with the use of a presumptive color test reagent, dimethylaminocinnamaldehyde (p-dmac). Twenty-five smokeless powders were tested using this reagent to evaluate the color change that would occur in the presence of nitroglycerin. All presumptive results were confirmed via gas chromatography–mass spectrometry. Highlights: Paradimethylaminocinnamaldehyde is presumptively used to differentiate between single-base and double-base smokeless powders. Nitroglycerin standard is prepared. Nitroglycerin standard is subjected to presumptive test. Nitroglycerin standard is subjected to confirmation test, GC–MS. Paradimethylaminocinnamaldehyde is presumptively used to detect nitroglycerin in double-base smokeless gun powder.